Вибір структури та розробка моделі системи керування мікрокліматом при ідентифікації теплиці в класі біотехнічних систем - Решетюк, В. М.; Мірошник, В. О.; Лендєл, Т. І.; Куляк, Б. В. (Energy and Automation, 2017)
CHOICE OF STRUCTURE AND DEVELOPMENT MODEL OF THE MICROCLIMATE CONTROL SYSTEM UNDER THE IDENTIFICATION OF THE GREENHOUSE IN THE CLASS OF BIOTECHNICAL SYSTEMS • V. Reshetiuk, V. Miroshnyk, T. Lendiel, B. Kuliak The aim of the study is to identify the parameters of a biotechnical object and to determine the method for constructing a system for automatic control of technological processes in structures of enclosed soil, taking into account information on the state of the plant. Research tasks. BTS for the cultivation of vegetable products in a complete set is a complex system consisting of the following elements: a biotechnical object (plant-greenhouse system), a subsystem of microclimate factors, a subsystem of environmental factors, a subsystem of economic efficiency factors, a subsystem of management, a subsystem of resource constraints, A subsystem of forecasting, as well as the phytomonitoring subsystem proposed by us. The main tasks that arise when managing such a complex object are: - Identification of the most effective control factors, their relationship to the overall management task; - Identification of the coordinates of the system, time, magnitude, shape and sign for the formation of control actions; - Identification of favorable (adverse) control factors; - Identification of methods and methods for reconfiguring the system with the aim of adapting it to new operating conditions. Conclusions and prospects. As a result of the research, the parameters of the greenhouse were identified as a biotechnical control object. That allowed to describe the main tasks that arise when managing such a complex object. A MIMO model is proposed for the BTS, which fully meets the functional requirements of the climate control system. Defined model structure (ARX) The advantage of this structure is the most accurate representation of the actual state of technological processes. A control algorithm (PID) has been chosen for the automation system of the construction of closed ground, which can operate within the limits of the proposed structures. A MIMO-model of microclimate management in the industrial premises of the greenhouse was developed. Such a model makes it possible to control the microclimate parameters in the greenhouse taking into account information on the state of the plant and can also be used for training the BPS management. The chosen method (MIMO-models) is a useful tool in the development of automated greenhouse management systems, in the structure of which the phytomonitoring subsystem is assumed.